PERANCANGAN DAN IMPLEMENTASI APLIKASI TOEFL PADA PERANGKAT ANDROID - Sari, Yolen Perdana (Jurnal Informatika Universitas Pamulang, 2018)
Mobile phone and its applications is growing rapidly after this millennium era. It seems not difficult to imagine that in the future we will bring a device other than as a technology in which the mobile communication device, is also capable of playing music and video DVDs, watch TV, play games, digital cameras, read books, guide maps, banking transaction, browsing , and so forth. One application of technology that is a trend today is the development of mobile application for Android devices. An open platform is provided by android so the application can made by developers. Mobile application that made in this Final Project is the application of the Test of English as a Foreign Language. TOEFL recommendation has been through in almost every educational institution, so there is some application that utilized TOEFL as a training tool that can improve their TOEFL score. Along with technological development in the modern era who want a service that is not limited by place and time, practice TOEFL can be made on mobile devices more flexible and efficient. Therefore constructed a TOEFL application using the Android operating system. The results of tests performed showed that these applications can run all the functions and features are as expected. Then the application is very helpful for the user in preparing their Toefl test.